Quo Vadis Justice Collaborator dalam Sistem Hukum Pidana Formil - Samsul Arifin; Ahmad Yulianto Ihsan (PMIH Untag Semarang, 2023)
The emergence of the term whistleblower and justice collaborator in law enforcement processes in Indonesia provides a new atmosphere, where someone who knows or is involved in the occurrence of a crime can assist law enforcement officials in uncovering true facts, for which reason the law rewards them. in the form of leniency in sentencing to the witnesses of the cooperating perpetrators. Departing from these facts, the questions in this research are (1) Institutions authorized to make someone involved in a crime a justice collaborator, (2) obtaining status as a justice collaborator. The method used in this research is normative legal research with the statute approach, case approach, and conceptual approach. The purpose of this research is to find out which institutions/agencies can make a person a justice collaborator in uncovering the occurrence of a crime.